Deteriorated Systolic Blood Pressure Recovery and Heart Rate Recovery After Graded Exercise in Children With Familial Mediterranean Fever - Havva EVRENGÜL; Selçuk YÜKSEL; Mustafa DOĞAN; Dolunay GÜRSES; Harun EVRENGÜL (Archives of Rheumatology, 2017)
Objectives: This study aims to investigate if cardiac involvement may occur in children with familial Mediterranean fever (FMF) without cardiovascular symptoms by using heart rate recovery (HRR) and systolic blood pressure recovery (SBPR) parameters. Patients and methods: A total of 50 FMF patients (26 males, 24 females; mean age 151±33.4 month; range 60 to 216 month) and 30 healthy controls (18 males, 12 females; mean age 143±43.9 month; range 84 to 228 month) were included in the study. All patients were evaluated by echocardiography. All patients underwent a maximal graded exercise stress test. HRR and SBPR parameters were calculated. Results: There was a significant decrease in HRR1 value in FMF group (p=0.03). SBPR1 and SPBR2 values were higher in FMF group compared to control group (0.96±0.12 vs 0.88±0.12 and 0.95±0.09 vs 0.91±0.11, respectively); and the high SBPR1 value was statistically significant (p=0.02). FMF presence had a negative correlation with HRR1 (r= -0.26, p=0.03) and a positive correlation with SBPR1 (r=0.29, p=0.02). There was a negative correlation of M694V homozygous mutation with HRR1 and HRR2 values (r= -0.43, p=0.004, r=-0.42, p=0.005). Conclusion: Cardiac involvement may occur in FMF patients without cardiovascular symptoms. Impaired SBPR and decreased HRR response may indicate increased cardiovascular risk in these patients despite normal exercise stress test results.